The warmer the weather, the more gram-negative bacteria - impact of temperature on clinical isolates in intensive care units. - Frank Schwab; Petra Gastmeier; Elisabeth Meyer (PLoS ONE)
Background We investigated the relationship between average monthly temperature and the most common clinical pathogens causing infections in intensive care patients. Methods A prospective unit-based study in 73 German intensive care units located in 41 different hospitals and 31 different cities with total 188,949 pathogen isolates (102,377 Gram-positives and 86,572 Gram-negatives) from 2001 to 2012. We estimated the relationship between the number of clinical pathogens per month and the average temperature in the month of isolation and in the month prior to isolation while adjusting for confounders and long-term trends using time series analysis. Adjusted incidence rate ratios for temperature parameters were estimated based on generalized estimating equation models which account for clustering effects. Results The incidence density of Gram-negative pathogens was 15% (IRR 1.15, 95%CI 1.10-1.21) higher at temperatures ≥ 20°C than at temperatures below 5°C. E. cloacae occurred 43% (IRR=1.43; 95%CI 1.31-1.56) more frequently at high temperatures, A. baumannii 37% (IRR=1.37; 95%CI 1.11-1.69), S. maltophilia 32% (IRR=1.32; 95%CI 1.12-1.57), K. pneumoniae 26% (IRR=1.26; 95%CI 1.13-1.39), Citrobacter spp. 19% (IRR=1.19; 95%CI 0.99-1.44) and coagulase-negative staphylococci 13% (IRR=1.13; 95%CI 1.04-1.22). By contrast, S. pneumoniae 35% (IRR=0.65; 95%CI 0.50-0.84) less frequently isolated at high temperatures. For each 5°C increase, we observed a 3% (IRR=1.03; 95%CI 1.02-1.04) increase of Gram-negative pathogens. This increase was highest for A. baumannii with 8% (IRR=1.08; 95%CI 1.05-1.12) followed by K. pneumoniae, Citrobacter spp. and E. cloacae with 7%. Conclusion Clinical pathogens vary by incidence density with temperature. Significant higher incidence densities of Gram-negative pathogens were observed during summer whereas S. pneumoniae peaked in winter. There is increasing evidence that different seasonality due to physiologic changes underlies host susceptibility to different bacterial pathogens. Even if the underlying mechanisms are not yet clear, the temperature-dependent seasonality of pathogens has implications for infection control and study design.